2007
DOI: 10.1890/1540-9295(2007)5[315:eiowed]2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Ecological impacts of wind energy development on bats: questions, research needs, and hypotheses

Abstract: At a time of growing concern over the rising costs and long‐term environmental impacts of the use of fossil fuels and nuclear energy, wind energy has become an increasingly important sector of the electrical power industry, largely because it has been promoted as being emission‐free and is supported by government subsidies and tax credits. However, large numbers of bats are killed at utility‐scale wind energy facilities, especially along forested ridgetops in the eastern United States. These fatalities raise i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
457
0
8

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 435 publications
(476 citation statements)
references
References 21 publications
(21 reference statements)
8
457
0
8
Order By: Relevance
“…Rydell et al (2010a,b) found that the bat genera at most risk of colliding with wind turbines in northwest Europe were Nyctalus, Pipistrellus and Vespertilio and to some extent also Eptesicus, all of which have long and narrow wings, forage in the open air and tend to be migratory. The North American bats most often killed at wind turbines are morphologically and ecologically similar to those in Europe, but belong to other genera (Lasiurus, Lasionycerteris and Perimyotis; Johnson et al 2004;Kunz et al 2007), features that are consistent with our study.…”
Section: Discussionsupporting
confidence: 89%
“…Rydell et al (2010a,b) found that the bat genera at most risk of colliding with wind turbines in northwest Europe were Nyctalus, Pipistrellus and Vespertilio and to some extent also Eptesicus, all of which have long and narrow wings, forage in the open air and tend to be migratory. The North American bats most often killed at wind turbines are morphologically and ecologically similar to those in Europe, but belong to other genera (Lasiurus, Lasionycerteris and Perimyotis; Johnson et al 2004;Kunz et al 2007), features that are consistent with our study.…”
Section: Discussionsupporting
confidence: 89%
“…Resource-based hypotheses of attraction include bats seeking shelter, social opportunities, or food at turbines (3,8,9,13), all of which may occur more often on the leeward sides of tall, tree-like structures. The simplest explanation for bats closely approaching turbines may be that they are seeking places to roost in what they perceive as trees while migrating.…”
Section: Discussionmentioning
confidence: 99%
“…energy development | sensory perception | video surveillance | wildlife | wind energy B ats are long-lived mammals with low reproductive potential and require high adult survivorship to maintain populations (1,2). The recent phenomenon of widespread fatalities of bats at utility scale wind turbines represents a new hazard with the potential to detrimentally affect entire populations (3,4). Bat fatalities have been found at wind turbines on several continents (3)(4)(5)(6), with hypothesized estimates of fatalities in some regions ranging into the tens to hundreds of thousands of bats per year (4,6).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Wind turbines do, however, have batrelated mortalities (Willis et al 2010;Arnett et al 2008;Kunz et al 2007), and the author wholeheartedly encourages research comparing bat fatalities across various energy sources. Indeed, evidence from Barclay et al (2007) compiled from 21 separate wind energy sites suggests that bat deaths may be as high as 1.46 per GWh.…”
Section: Limitationsmentioning
confidence: 99%